2013
DOI: 10.1159/000351404
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Effect of a New Intranasal Therapy (MP29-02) in Allergic Rhinitis Assessed by Responder Analysis

Abstract: Background: It is unclear what constitutes a clinically meaningful response for allergic rhinitis (AR) outcomes. The objectives of these post hoc analyses were (1) to define a clinically meaningful response using novel efficacy analyses (including a responder analysis), and (2) to compare the efficacy of MP29-02 [a novel intranasal formulation of azelastine hydrochloride (AZE) and fluticasone propionate (FP)] with commercially available FP, AZE and placebo in seasonal AR (SAR) patients, using these novel analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
138
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 56 publications
9
138
3
3
Order By: Relevance
“…Earlier real‐world studies in patients with moderate‐to‐severe AR found mean reductions in VAS score over approximately 14 days of 31,8 50,9 54,6 and >60 points,7 demonstrating a consistent pattern of substantial improvement in symptoms with MP‐AzeFlu therapy. These findings are consistent with earlier clinical trials of MP‐AzeFlu that found significantly greater reductions in nasal symptoms, including nasal congestion, with MP‐AzeFlu than with FP alone 10, 11…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Earlier real‐world studies in patients with moderate‐to‐severe AR found mean reductions in VAS score over approximately 14 days of 31,8 50,9 54,6 and >60 points,7 demonstrating a consistent pattern of substantial improvement in symptoms with MP‐AzeFlu therapy. These findings are consistent with earlier clinical trials of MP‐AzeFlu that found significantly greater reductions in nasal symptoms, including nasal congestion, with MP‐AzeFlu than with FP alone 10, 11…”
Section: Discussionsupporting
confidence: 91%
“…Optimal pharmacotherapy for PER will not only control symptoms but also help patients function better (via improved sleep) and improve their quality of life. The findings of this study, which add to the body of evidence of previous real‐world and clinical studies of MP‐AzeFlu,6, 7, 8, 9, 10, 11, 29, 30, 31 further support MP‐AzeFlu as a treatment with broad benefits for this patient population.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…12 In adults and adolescents, MP-AzeFlu provides twice the nasal and ocular symptom relief as INS or intranasal antihistamine monotherapy, and better long-term nasal symptom relief than FP in adults with perennial AR (PAR) or non-AR. 13,14 Its short-and long-term safety in these populations is well established. 13,15,16 The short-and long-term efficacy of MP-AzeFlu in pediatric AR has also been assessed.…”
mentioning
confidence: 99%